Line excitation array detection fluorescence microscopy at 0.8 million frames per second. Issue 1 (December 2018) - Martin, Chris; Li, Tianqi; Hegarty, Evan; Zhao, Peisen; Mondal, Sudip; Ben-Yakar, Adela
Abstract Three-dimensional, fluorescence imaging methods with ~1 MHz frame rates are needed for high-speed, blur-free flow cytometry and capturing volumetric neuronal activity. The frame rates of current imaging methods are limited to kHz by the photon budget, slow camera readout, and/or slow laser beam scanners. Here, we present line excitation array detection (LEAD) fluorescence microscopy, a high-speed imaging method capable of providing 0.8 million frames per second. The method performs 0.8 MHz line-scanning of an excitation laser beam using a chirped signal-driven longitudinal acousto-optic deflector to create a virtual light-sheet, and images the field-of-view with a linear photomultiplier tube array to generate a 66 × 14 pixel frame each scan cycle. We implement LEAD microscopy as a blur-free flow cytometer forCaenorhabditis elegans moving at 1 m s−1 with 3.5-µm resolution and signal-to-background ratios >200. Signal-to-noise measurements indicate future LEAD fluorescence microscopes can reach higher resolutions and pixels per frame without compromising frame rates. Demanding biological imaging applications require extremely fast detection methods. Here, the authors demonstrate Line Excitation Array Detection, their developed technique for performing fluorescence microscopy in 3D with 0.8 million frames per second, by applying it to flow cytometry and neuron detection.